2022
DOI: 10.1177/02646196221077215
|View full text |Cite
|
Sign up to set email alerts
|

The effects of balance and core stability training on postural control in people with visual impairment: A systematic review

Abstract: Visual impairment is one of the most common functional impairments that considerably affects the postural control process and the ability to maintain balance. The purpose of this study was to perform a systematic review concerning the effects of balance and core stability training on postural control in individuals who are visually impaired. This article comprehensively reviewed studies on balance in individuals who are blind from the following databases: PubMed, Embase, Web of Science, and Scopus from 2007 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…An improvement in static balance ability because of core balance training has been confirmed in several studies [21,[33][34][35]. Furthermore, core strengthening presents certain benefits; these data alone were insufficient to confirm dynamic balance's effects on university judo athletes [36].…”
Section: Discussionmentioning
confidence: 95%
“…An improvement in static balance ability because of core balance training has been confirmed in several studies [21,[33][34][35]. Furthermore, core strengthening presents certain benefits; these data alone were insufficient to confirm dynamic balance's effects on university judo athletes [36].…”
Section: Discussionmentioning
confidence: 95%
“…Vestibular stimulation rehabilitation reportedly improves the postural stability of visually impaired individuals, bringing it at par with that of individuals with normal vision [ 32 ]. A systematic review showed that a minimum of six weeks of balance and core stability training could beneficially influence fall risk in visually impaired individuals, irrespective of age, sex, or visual impairment severity [ 33 ]. Hence, exercises that stimulate the vestibular system through head and body movements are recommended to improve balance in visually impaired individuals.…”
Section: Discussionmentioning
confidence: 99%